2012
DOI: 10.1093/rpd/ncs086
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of energy response of Al2O3:C optically stimulated luminescent dosemeters (OSLDs) using cavity theory

Abstract: Aluminium oxide (Al(2)O(3):C) is a common material used in optically stimulated luminescent dosemeters (OSLDs). OSLDs have a known energy dependence, which can impact on the accuracy of dose measurements, especially for lower photon energies, where the dosemeter can overrespond by a factor of 3-4. The purpose of this work was to characterise the response of Al(2)O(3):C using cavity theory and to evaluate the applicability of this approach for polyenergetic photon beams. The cavity theory energy response showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…For kV photons, TLDs over‐respond by a factor of up to 1.4 relative to 60 Co. Of note, this beam quality dependence can vary with different sizes and shapes of TLD. The magnitude of over‐response to low‐energy beams is much greater for OSLDs, which over‐respond by a factor of as much as 3 to 4 relative to 60 Co . If the calibration is done in a kV environment, the beam quality correction factor will be less.…”
Section: Specific Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For kV photons, TLDs over‐respond by a factor of up to 1.4 relative to 60 Co. Of note, this beam quality dependence can vary with different sizes and shapes of TLD. The magnitude of over‐response to low‐energy beams is much greater for OSLDs, which over‐respond by a factor of as much as 3 to 4 relative to 60 Co . If the calibration is done in a kV environment, the beam quality correction factor will be less.…”
Section: Specific Applicationsmentioning
confidence: 99%
“…For kV photons, TLDs over-respond by a factor of up to 1.4 52,162 relative to 60 Co. Of note, this beam quality dependence can vary with different sizes and shapes of TLD 145 . The magnitude of over-response to low-energy beams is much greater for OSLDs, which over-respond by a factor of as much as 3 to 4 relative to 60 Co. 21,41,44,51,59,[163][164][165][166] If the calibration is done in a kV environment, the beam quality correction factor will be less. However, a beam quality correction factor may still be substantial (particularly for OSLDs) between the calibration and experimental irradiation conditions as the energy response changes substantially even with small changes in beam quality in the kV energy range.…”
Section: E Imagingmentioning
confidence: 99%
“…A second major concern is that Al 2 O 3 over-responds to low energy photons (with respect to water or tissue) because of its relatively large effective atomic number. 10,14,16,17,24 Per milligray of dose delivered to water, the response of Al 2 O 3 can be larger by a factor of 3.5 or more due to increased photoelectric effect at low energies. While this issue has been identified in the literature, [24][25][26] and has been examined for some cone-beam CT scans, 20 a thorough study of appropriate correction factors in a diagnostic CT environment has not been done.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the high‐sensitivity LiF:Mg,Cu,P (MCPN‐TLDs) have been the subject of fewer studies, but these detectors have shown a comparably lower energy sensitivity (~−20% relative to 60 Co, or ~50% that of MTS‐N TLDs) in the same kilovoltage x‐ray energy range . In contrast, Monte Carlo models and experimental investigations have shown that Al 2 O 3 :C OSLD‐absorbed dose sensitivities are up to 350–400% higher at x‐ray kilovoltage energies than at megavoltage x‐ray energies …”
Section: Introductionmentioning
confidence: 99%
“…Many other kilovoltage x‐ray applications, such as orthovoltage x‐ray therapy or animal research irradiation techniques, operate at much higher (150–300 kVp) energy ranges . Studies that investigate broadbands of energies tend to focus on Monte Carlo simulations for monoenergetic photons rather than simulating plausible polyenergetic spectra found in real x‐ray sources . Although OSLDs are increasingly being used for image‐guided animal irradiations at kilovoltage energies, a comprehensive, empirical, systematic review of the energy dependence of OSLDs has not yet been published.…”
Section: Introductionmentioning
confidence: 99%